2005
DOI: 10.1161/circulationaha.105.578492
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bare-Metal Stenting With Minimally Invasive Bypass Surgery for Stenosis of the Left Anterior Descending Coronary Artery

Abstract: Background-Randomized trials comparing stenting with minimally invasive direct coronary artery bypass surgery in patients with isolated proximal left anterior descending lesions have shown a significantly higher reintervention rate for stenting and similar results for mortality and reinfarction at short-term follow-up. Long-term follow-up data are sparse. Methods and Results-Patients with isolated proximal left anterior descending stenosis were randomized to either surgery (nϭ110) or bare-metal stenting (nϭ110… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 37 publications
2
19
1
4
Order By: Relevance
“…Both treatment strategies effectively reduce symptoms (3). Randomized trials comparing both strategies revealed a significantly higher reintervention rate after stenting and similar results for mortality and reinfarction at mid-to long-term follow-up (4,5).…”
Section: Discussionmentioning
confidence: 89%
“…Both treatment strategies effectively reduce symptoms (3). Randomized trials comparing both strategies revealed a significantly higher reintervention rate after stenting and similar results for mortality and reinfarction at mid-to long-term follow-up (4,5).…”
Section: Discussionmentioning
confidence: 89%
“…It is well known that LITA-LAD bypass is superior to PCI in terms of the need for reintervention. According to various reports, revascularization after PCI/MIDCAB was required for 13.3-27.9/6.6%-8.4% of patients at 6 months, 5,21 16.2/4.2% at 1 year, 47 24.2/0% at 3.4 years, 48 and 32/10% at 5 years. 49 A relatively new drug-eluting stent is now used for such patients to prevent restenosis of the targeted lesion.…”
Section: Discussionmentioning
confidence: 99%
“…However, in patients with normal left ventricular systolic function and single-or two-vessel CAD not involving the left anterior descending coronary artery (LAD), there is no evidence to suggest that CABG is beneficial over PCI [20••]. In patients with proximal LAD disease, PCI with BMS and CABG (including minimally invasive CABG) appear to be equivalent in terms of mortality benefit, although there is a lower rate of repeat revascularization with CABG [45][46][47][48]. Nonetheless, in the modern era of PCI with DES, the repeat revascularization advantage of CABG over PCI may be reduced or nonexistent in patients with proximal LAD disease.…”
Section: Medical Therapy: As Good As Revascularization?mentioning
confidence: 99%